2000
DOI: 10.1038/sj.bmt.1702165
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the serotherapy regimen used and the marrow cell dose received on rejection, graft-versus-host disease and outcome following unrelated donor bone marrow transplantation for leukaemia

Abstract: Summary:Unrelated donor (UD) transplantation is the only potentially curative therapy for many leukaemia patients but is associated with a high mortality and morbidity. We sought to identify factors that could be optimised to improve outcome following UD transplantation in adults. Data was retrospectively analysed on 55 patients sequentially receiving UD transplants for CML or acute leukaemia (AL), all of whom received serotherapy for the prevention of GVHD and rejection. All patients received standard conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 44 publications
4
51
0
Order By: Relevance
“…Although many studies reported that higher cell dose improved OS rates, 8,11,12,18,19 effects of cell dose on relapse and NRM rates were not consistent among studies probably because of the differences in diseases, stages and transplant procedures. Furthermore, it is not practical to analyze child and adult patients together because biology of disease, treatment protocols and harvested total nucleated cells per body wt are likely to differ between them.…”
Section: Discussionmentioning
confidence: 90%
“…Although many studies reported that higher cell dose improved OS rates, 8,11,12,18,19 effects of cell dose on relapse and NRM rates were not consistent among studies probably because of the differences in diseases, stages and transplant procedures. Furthermore, it is not practical to analyze child and adult patients together because biology of disease, treatment protocols and harvested total nucleated cells per body wt are likely to differ between them.…”
Section: Discussionmentioning
confidence: 90%
“…However, recent data from single institutions have shown outcomes after UD BMT approaching those achieved from MRD transplants. 1,8,11 These improved results appear to be at least partly due to improved matching techniques. For example, both acute GVHD and TRM are significantly less after transplants from UD matched by molecular methods for class II antigens.…”
Section: Discussionmentioning
confidence: 93%
“…6 In recent years, a number of European centers have reported relatively low rates of acute GVHD and early TRM using a variety of ATG products and schedules of administration. [7][8][9][10][11][12][13][14][15] Total doses of pretransplant thymoglobulin have ranged between 8 and 20 mg/kg. 8,9,12,13 An IBMTR analysis of alternative donor transplants between 1987 and 1993 indicated that the influence of donors on outcome was not apparent in high risk patients but quite significant with low and intermediate risk disease.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…In unrelated donor transplants, the use of ATG for in vivo T-cell depletion was found to be useful by some but not by others 25,26 Bacigalupo et al 27 reported a randomized prospective study of the use of ATG in unrelated donor marrow transplantation and found that though the risk of grade III-IV acute GVHD is markedly reduced in the ATG cohort, this does not result in the reduction of treatment-related mortality because of an increased risk of infections. They also noted that though the survival is unchanged, extensive chronic GVHD is significantly reduced in patients receiving ATG.…”
Section: Discussionmentioning
confidence: 99%